Effect of Seed Size and Sowing Depth on Germination and Seedling Growth of Colophospermum mopane (Kirk Ex Benth.) Kirk Ex J. Le'on - Nagarajan, M.; Mertia, R. S. (Indian Forester, 2006)
An experiment was conducted to determine the effect of sowing depth and seed size on germination and growth of Colophospermum mopane. Out of the three seed sizes and four depth of sowing large sized seed sown at 5 mm depth showed significant increase in mean germination per cent, daily germination, germination value, shoot/root length and dry matter production than the other two type of seeds viz.,elongated small size and round shape seeds sown at deeper depth. The study revealed that shallow sowing depth and large seeds can be used for better nursery raising for this species